Rhinovirus Infection and Familial Atopy Predict Persistent Asthma and Sensitisation 7 Years after a First Episode of Acute Bronchiolitis in Infancy - Julie Magnier; Valérie Julian; Aurélien Mulliez; Alexandra Usclade; Emmanuelle Rochette; Bertrand Evrard; Flore Amat; Carole Egron (Children, 2021)
Background: We set out to assess the risk factors for asthma outcome in a cohort of infants who experienced their first episode of acute bronchiolitis. Methods: A cohort of 222 infants who were included during a first episode of acute bronchiolitis was prospectively followed. Herein, we present the results of their assessments (symptom history, skin prick tests, specific IgE assay, respiratory function tests) at age seven. Results: Of the 68/222 (30.6%) children assessed at age seven, 15 (22.05%) presented with asthma and were mainly males (p = 0.033), 14 (20%) had respiratory allergies, 17 (25%) presented atopic dermatitis and none had a food allergy. Family history of atopy was associated with asthma and sensitisation to aeroallergens at age seven (p = 0.003, p = 0.007). Rhinovirus (hRV) infection and rhinovirus/respiratory syncytial virus (RSV) co-infection were significantly associated with asthma at age seven (p = 0.035, p = 0.04), but not with the initial severity of bronchiolitis. Eosinophil counts at ages three and seven were significantly higher in the asthmatics (p = 0.01, p = 0.046). Conclusion: Any infant, especially male, presenting a first episode of acute bronchiolitis due to hRV with a family history of atopy should be closely monitored via follow-up due to a higher risk for asthma at school age.